Geomagnetic variations induced by the partial solar eclipse of November 25, 2011 - Juan A. LAZZÚS; Ignacio SALFATE (Contributions to Geophysics and Geodesy, 2025)
We examine the geomagnetic variations observed from the SAMBA network during the partial solar eclipse on November 25, 2011, in Antarctica. The eclipse reached nearly 90% obscuration in the western Antarctic Peninsula at the point of greatest eclipse at 06:21 UTC. Six magnetic ground stations distributed across Chile and Antarctica, around 0° longitude and at various latitudes, were used to collect geomagnetic field data in X, Y, and Z coordinates at a 1-second resolution. A baseline from the international Q-days of the month was applied to filter out isolated signals caused by the eclipse. Results indicated a systematic decrease in both the X and Y components, synchronized with the passage of the penumbra.